The effects of cervical muscle fatigue on balance - A study with elite Amateur Rugby League players - Gosselin, G.; Fagan, M. J. (Journal of Sports Science & Medicine, 2014)
Neck muscle fatigue has been shown to alter an individual`s balance in a similar way to that reported in subjects suffering from neck pain or subjects that have suffered a neck injury. The main purpose of the present study was to quantify the effects of neck fatigue on neck muscle electromyography (EMG) activity, balance, perceived fatigue and perceived stability. Forty four elite amateur rugby league players resisted with their neck muscles approximately 35% maximum voluntary isometric contraction (MVIC) force for 15 minutes in eight different directions. Sway velocity and surface electromyography were measured. Questionnaires were used to record perceived effort and stability. Repeated measures ANOVA showed that after 15 minutes isometric contraction, significant changes were seen in sway velocity, perceived sway and EMG median frequency. There were no differences in perceived efforts. The changes in sway velocity and median frequency were more pronounced after extension and right and left posterior oblique contractions but there was no significant difference in sway velocity after contraction in the right lateral flexion, right anterior oblique and left anterior oblique direction of contraction. All the subjects showed oriented whole-body leaning in the plane of the contraction. The experiment produced significantly altered and perceived altered balance in this group of physically fit individuals. The results may contribute to our understanding of normal functional capacities of athletes and will provide a basis for further investigation in healthy non-athletes and participants that have suffered neck injuries. This may ultimately help develop accurate and valid rehabilitation outcome measures.